Acute fatty liver of pregnancy: case report - Vilela,Fernanda (2017)
Acute fatty liver of pregnancy (AFLP) is a rare and life-threatening disorder. The etiology of AFLP is still unclear, however recent studies demonstrated association with long-chain 3-hydroxyacyl-CoA dehydrogenase deficiency1-3. In this report we describe a 27-year-old woman that presented at 38 weeks of gestation in spontaneous labour. She underwent emergency caesarean for non-reassuring fetal heart tracing. After caesarean the patient developed confusion, tremor, vomits and pruritus. She also presented jaundice and choluria. Laboratory data revealed hepatic dysfunction and imaging exams demonstrated hepatic lipid infiltration. The diagnosis of AFLP was defined based on clinical, laboratory and ultrasound findings and was confirmed by liver biopsy. She was successfully treated with supportive therapy. This case report reinforces the importance of recognition of clinical, laboratory and imaging findings suggestive of AFLP and demonstrates that early diagnosis and prompt supportive therapy improve the outcome reducing maternal and neonatal mortality1,4